Psammotourism: Desert sand as a specific resource and touristic experience - Laurent Gagnol; Pierre-Antoine Landel (Via@, 2016)
This article describes the conditions for the emergence of a new local territorial resource that is based on the exploitation of the presence of sand dunes and examines its construction. Merzouga, located in the pre-Saharan desert of southeast Morocco, has become a global hotspot for desert tourism. The touristic immersion in the sand here is twofold. There is the classic excursions type of tourism, aimed at an international clientele, and the wellness tourism, aimed at Moroccan therapy enthusiasts, which consists of the practice of sand baths. The sand resource is linked up with other cultural and identity-related resources, which anchor it locally and make it a specific territorial resource that is locally controlled and recognised externally. However, the massification of psammotourism, through most notably the creation of a ‘desertfront’ (akin to a holiday resort’s seafront), threatens to banalise the resources that have made this tourist destination so unique and so successful.